REPUTATION BRAND ISLAMIC BANKING IN INDONESIA - Yenti Afrida; Zaky Mubarak Lubis; Seppi Mustion; Azlin Alisha Ahmad; Nurhayati Nurhayati (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research examines how customers who use mobile banking services perceive the brand image of Islamic banks in Indonesia. It applies a qualitative content analysis approach using thematic analysis in NVivo. This analysis focuses on the mobile banking apps of Islamic banks in Indonesia. This research analyzed and visualized coded data to identify patterns in perceptions, levels of satisfaction, and complaints about digital Islamic banking services. This research found that the main components of Islamic bank brand reputation are operational responsiveness and operational efficiency of the services, alongside trust and transparency. Customers of Islamic banks perceive that compliance with Sharia principles and Islamic values is a given. Therefore, Islamic values and Sharia compliance do not enhance the bank's reputation. The data analysis found that customers appreciate banks that provide consistent, reliable service. Customers consider deep digital services critical, but still prioritize transaction reliability, security, and service quality as the most influential factors in the banking service brand reputation. Thus, for Islamic banks to provide professional, secure, and customer-oriented services and to integrate Sharia values, their brand reputation must be sustained. This research offers both a theoretical contribution to the scholarship on brand reputation in Islamic banking and a consolidated, practical, service, and reputation strategy for the digital age.